The Australian sport field: moving and watching. Issue 1 (May 2018) - Gayo, Modesto; Rowe, David
The Australian sport field (as in other countries) is powerfully influenced by the media field, and for this reason, the survey on which this article is based placed considerable emphasis on mediated spectatorship. The survey, which draws on and adapts the work of Pierre Bourdieu, revealed differences in the place of sport in the lives of respondents, with a majority never playing it, but an even larger majority watching sport through the media, especially television. Positions within the sport field can, like others, be represented as a set of clusters or divided into quadrants where variable cultural practices; degrees of cultural, educational, social and economic capital; and social characteristics are thrown into sharp relief. This article teases out such differences in relations and practices within the sport field, explores knowledge and taste with regard to playing and watching sport in Australia, and questions the relationship between sport and national culture.